Rythm of the eyes: enhancing visual communication through eye-tracking technology - Abu Bakar, Shamsul; Miller, Patrick A. (Universiti Putra Malaysia Press, 2014)
Visual is the main form of communication used by designers to convey unique and creative messages to the viewers. Whether the communication processes took place in basic forms such as in 2D sketches, paintings or through rendered 3D animated models, the ultimatum of using visual communication is to enhance the viewers experience with the tangible creative products and subsequently improve the quality of their decision-making. The platforms for visual communication within the creative environment also include advanced visualization technologies such as virtual reality and augmented reality, which provide real-time and real-world experience to the viewers. Nevertheless questions were raised whether the designers were fully aware of the viewers perception towards the visual information embedded in their creative products. Without these understanding, the products and their valuable information would be less meaningful to the viewers.